Aktywność fizyczna u młodzieży ponadgimnazjalnej Zespołu Szkół Chemicznych w Bydgoszczy = Physical activity at school youth team Chemical Schools in Bydgoszcz - Pluta, Agnieszka; Jaczek–Kierzenkowska, Jolanta; Faleńczyk, Kamila; Budnik-Szymoniuk, Maria; Basińska-Drozd, Halina; Kujawa, Wiesława (Journal of Education, Health and Sport, 2016)
Pluta Agnieszka, Jaczek-Kierzenkowska Jolanta, Faleńczyk Kamila, Budnik-Szymoniuk Maria, Basińska-Drozd Halina, Kujawa Wiesława. Aktywność fizyczna u młodzieży ponadgimnazjalnej Zespołu Szkół Chemicznych w Bydgoszczy = Physical activity at school youth team Chemical Schools in Bydgoszcz. Journal of Education, Health and Sport. 2016;6(7):556-565. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.59125 http://ojs.ukw.edu.pl/index.php/johs/article/view/3720 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.07.2016. Revised 25.07.2016. Accepted: 28.07.2016. Aktywność fizyczna u młodzieży ponadgimnazjalnej Zespołu Szkół Chemicznych w Bydgoszczy Physical activity at school youth team Chemical Schools in Bydgoszcz Agnieszka Pluta1, Jolanta Jaczek-Kierzenkowska2, Kamila Faleńczyk1, Maria Budnik‑Szymoniuk1, Halina Basińska-Drozd, Wiesława Kujawa1,2 1Zakład Pielęgniarstwa Społecznego Collegium Medicum w Bydgoszczy Uniwersytetu Mikołaja Kopernika w Toruniu 2WOZ "GRYF-MED" w Bydgoszczy 1Department of Community Nursing Faculty of Health Sciences Collegium Medicum in Bydgoszcz of the Nicolaus Copernicus University in Toruń 2WOZ”GRYF-MED” In Bydgoszcz Słowa kluczowe: aktywność fizyczna, ruch, młodzież. Keywords: physical activity, movement, youth. Abstract Introduction. Physical activity is any body movement necessary for daily life or part of the exercise program. In addition to nutrition is a key determinant of health at every stage of human life. Particularly important in childhood and adolescence, when it is essential for the proper development of both physical, biological and motor. Increased motor activity is beneficial to a number of characteristics not only of physiological and immunological but adaptive as well as the correct course of a number of metabolic and hormonal processes. Material and methods. The study included the number of 100 students in grades Baccalaureate School of Chemical in Bydgoszcz. The work as a research tool used by his own questionnaire and the analysis of reporting forms from the study screening and health surveillance. The aim of this study was to assess physical activity in school youth. Results. Youth male accounted for most of the study group - 54 persons (54.0%). The test young people were divided into two age: 19 years and 20 years. Most were 19 - year olds - 59 persons (59.0%). Conclusions. The level of activity of youth is insufficient. Slightly higher levels of physical activity showed girls deficient weight and rural residents. The lowest level of physical activity presented overweight people. Streszczenie Wprowadzenie. Aktywność fizyczna to każdy ruch ciała konieczny do codziennego życia lub część programu ćwiczeniowego. Obok odżywiania jest kluczowym czynnikiem determinującym zdrowie na każdym etapie życia człowieka. Szczególnego znaczenia nabiera w dzieciństwie i młodości, kiedy jest niezbędna dla prawidłowego rozwoju zarówno fizycznego, biologicznego jak i motorycznego. Zwiększona aktywność ruchowa wpływa korzystnie na szereg właściwości nie tylko fizjologicznych, ale i odpornościowych, adaptacyjnych, a także na prawidłowy przebieg szeregu procesów metabolicznych i hormonalnych. Materiał i metoda. Badaniami objęto liczbę 100 uczniów klas maturalnych Zespołu Szkół Chemicznych w Bydgoszczy. W pracy jako narzędzie badawcze wykorzystano kwestionariusz ankiety własnego autorstwa oraz analizę formularzy sprawozdawczych z przeprowadzonych badań przesiewowych i profilaktycznych badań lekarskich. Cel. Celem niniejszej pracy była ocena aktywności fizycznej u młodzieży ponadgimnazjalnej. Wyniki. Młodzież płci męskiej stanowiła większość w badanej grupie – 54 osoby (54,0%). Badaną młodzież podzielono na dwie grupy wiekowe: 19 lat i 20 lat. Większość stanowili 19 - latkowie – 59 osób (59,0%). Wnioski. Poziom aktywności młodzieży jest niewystarczający. Nieznacznie wyższy poziom aktywności fizycznej wykazywały dziewczęta z niedoborem masy ciała oraz mieszkańcy wsi. Najniższy poziom aktywności fizycznej prezentowały osoby z nadwagą.